The Trend of Earnings Management Practices in the Indian Financial Sector - Kumari, Prity; Pattanayak, J. K. (Indian Journal of Finance, 2015)
Focusing on the importance of financial disclosure practices and corporate governance mechanism in the current business scenario, this study attempted to analyze the trends of earnings management practices among the financial sector firms in India. The Indian financial sector comprises of the banking and non banking services, securities investment services, fee based financial services, and finance related allied activities. A sample of 43 firms was selected for the study based on companies that were high on market capitalization, and the analysis was carried out for a period of 13 years (2000-2013) by utilizing CMIE Prowess 4.14 database. The findings of the study revealed that there was an existence of earnings management practices through management of discretionary accruals in the Indian financial sector firms, which followed a mixed trend.